Involuntary Vocalisations and a Complex Hyperkinetic Movement Disorder Following Left Side Thalamic Haemorrhage - T. Dietl; D. P. Auer; S. Modell; C. Lechner; C. Trenkwalder (Behavioural Neurology)
A variety of involuntary speech phenomena as for example palilalia have been described as consequences of neurological disorders. Palilalia is the involuntary repetition of syllabels, words and phrases in ongoing speech. We describe a 73 year old woman who suffered from a hypertensive thalamic haemorrhage. MRI revealed that the lesion was predominantly located within the pulvinar, extending to the lateroposterior thalamic nuclei and to the pretectal area with possible involvement of the medial geniculate body. Few months after the event she developed involuntary vocalisations with whole words and meaningless syllables being rapidly reiterated. In contrast to typical palilalia these vocalisations were not meaningfully related to the ongoing speech of the patient. In addition, the patient developed a complex hyperkinetic movement disorder with right-sided painful hemidystonia and bilateral clonic jerks and a right-sided postural tremor.